Sero-prevalance of Cryptococcal Antigenemia in HIV Positive Individual having CD4 Counts - Khadka, Sundar; Kandel, Samikshya; Pandit, Roshan; Manjhi, Rosham; Dhital, Subhash; Baniya, Jagat Bahadur; Mishra, Shravan Kumar; Mahato, Raj Kumar (Nepal Journal of Biotechnology, 2021)
Cryptococcus neoformans is one of the foremost common opportunistic infectious agents in people living with Acquired Immuno Deficiency Syndrome (AIDS). It has been reported to cause about 1 million cases of cryptococcal meningitis per year among HIV/AIDS and 600,000 deaths annually. This study was done to find the prevalence of Cryptococcal antigenemia among HIV positive individuals having CD4counts